Reverse Shoulder Arthroplasty, Deltopectoral Approach vs. Anterosuperior Approach: An Overview of the Literature - Georgoulas, Paraskevas; Fiska, Aliki; Ververidis, Athanasios; Drosos, Georgios I.; Perikleous, Evanthia; Tilkeridis, Konstantinos (Frontiers in Surgery, 2021)
Reverse shoulder arthroplasty has become an optimal treatment for numerous orthopedic entities, such as rotator cuff tear arthropathies, pseudoparalysis, fracture sequelae, acute fractures, failed arthroplasties, osteoarthritis, and rheumatoid arthritis; and is linked with relief of topical pain and regaining of functionality. Presently, reverse shoulder arthroplasty has been conducted through anterosuperior or deltopectoral approaches. Aim of the study was to discuss both approaches and to examine broadly their features in order to render a comparison in terms of clinical effectiveness. An electronic search in PubMed, EMBASE, and Google Scholar databases was performed, using combinations of the following keywords: reverse shoulder arthroplasty, deltopectoral approach, anterosuperior approach, notching, and cuff tear arthropathy. A total of 61 studies were found, and 16 relevant articles were eventually included. Currently published literature has not shown significant diversities in clinical course due to approach preference; risk of instability seems to be greater in deltopectoral approach, while regarding scapular notching and fracture rates the findings were conflicted. In addition, anterosuperior approach has been associated with decreased risk of acromial and scapular spine fractures. In conclusion, both surgical approaches have shown similar clinical outcomes and effectiveness concerning pain and restoring range of motion in rotator cuff tear arthropathies. In future, further investigations based on large-scale well-designed studies are required to address clinical gaps allowing in-depth comparison of both approaches.